2014
DOI: 10.1080/21501203.2014.899525
|View full text |Cite
|
Sign up to set email alerts
|

Association of genotypes with infection types and antifungal susceptibilities inCandida albicansas revealed by recent molecular typing strategies

Abstract: Candida albicans is a commensal microorganism in the mucosa of healthy individuals, but is also the most common opportunistic fungal pathogen of humans. It causes from benign infections such as oral and vaginal candidiasis to fatal, systematic diseases in immunocompromised or critically ill patients. In addition to improved therapy, the rapid and accurate identification of the disease-causing strains is crucial for diagnosis, clinical treatment and epidemiological studies of candidiasis. A variety of methods f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…It shows that the risk of VVC in prevalent genotype was 4.3 times higher than that in other genotypes after controlling for age, marital, and sexual factors. CAI microsatellite genotyping has repeatedly been proven to be a powerful method for epidemiology of C. albicans (Bai, ). This approach revealed a significantly larger diversity than classical typing using 25S rDNA introns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It shows that the risk of VVC in prevalent genotype was 4.3 times higher than that in other genotypes after controlling for age, marital, and sexual factors. CAI microsatellite genotyping has repeatedly been proven to be a powerful method for epidemiology of C. albicans (Bai, ). This approach revealed a significantly larger diversity than classical typing using 25S rDNA introns.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 57 microsatellite genotypes revealed in this study, 12 seemed to have a global distribution, because the same genotypes were reported in Europe (Kageyama et al, ). Thirty‐six genotypes were shared between Beijing/Tianjing, Guangdong, Guiyang, and Wuhan, representing northern, southern, western, and central regions of China, respectively (Bai, ; Fan et al, ; Ge et al, ). Seven novel genotypes were recognized in the current study, which seemed to have a local distribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The welldifferentiated, cryptic species, C. albicans and C. dubliniensis showed differences in virulence (Gilfillan et al 1998). Within C. albicans in China, it has been reported that different genotypes associate with different phenotypes of disease presentation and antifungal resistance (Bai 2014), and that his association can involve clades of pathogenic strains that are geographically distinct (Ge et al 2012). European C. albicans has also shown association between genotype and antifungal resistance, as well as cellsurface repeats, but not pathogenicity (Odds 2010).…”
Section: Population Geneticsmentioning
confidence: 99%